Global generalized solvability in a strongly degenerate taxis-type parabolic system modeling migration–consumption interaction - Winkler, Michael (Zeitschrift für angewandte Mathematik und Physik)
Abstract The parabolic problem $$\begin{aligned} \left\{ \begin{array}{l} u_t=\Delta \big (u\phi (v)\big ), \\ v_t=\Delta v-uv, \end{array} \right. \end{aligned}$$ u t = Δ ( u ϕ ( v ) ) , v t = Δ v - u v , is considered in smoothly bounded subdomains of $${\mathbb {R}}^n$$ R n with arbitrary $$n\ge 1$$ n ≥ 1 . Under the assumptions that $$\phi \in C^0([0,\infty )) \cap C^3((0,\infty ))$$ ϕ ∈ C 0 ( [ 0 , ∞ ) ) ∩ C 3 ( ( 0 , ∞ ) ) is positive on $$(0,\infty )$$ ( 0 , ∞ ) and satisfies $$\begin{aligned} \liminf _{\xi \searrow 0} \frac{\phi (\xi )}{\xi ^\alpha }>0 \quad {\text{ and }} \quad \limsup _{\xi \searrow 0} \big \{ \xi ^\beta |\phi '(\xi )| \big \}<\infty \end{aligned}$$ lim inf ξ ↘ 0 ϕ ( ξ ) ξ α > 0 and lim sup ξ ↘ 0 { ξ β | ϕ ′ ( ξ ) | } < ∞ with some $$\alpha >0$$ α > 0 and $$\beta >0$$ β > 0 , for all reasonably regular initial data an associated no-flux type initial-boundary value problem is shown to admit a global solution in an appropriately generalized sense. This extends previously developed solution theories on problems of this form, which either concentrated on non-degenerate or weakly degenerate cases corresponding to the choices $$\alpha =0$$ α = 0 and $$\alpha \in (0,2)$$ α ∈ ( 0 , 2 ) , or were restricted to low-dimensional settings by requiring that $$n\le 2$$ n ≤ 2 .

Refined regularity analysis for a Keller-Segel-consumption system involving signal-dependent motilities - Li, Genglin; Winkler, Michael (Applicable Analysis)

A quantitative strong parabolic maximum principle and application to a taxis-type migration–consumption model involving signal-dependent degenerate diffusion - Winkler, Michael (Annales de l'Institut Henri Poincaré C, Analyse non linéaire)
The taxis-type migration–consumption model accounting for signal-dependent motilities, as given by u_{t} = \Delta (u\phi(v)) , v_{t} = \Delta v-uv , is considered for suitably smooth functions \phi\colon[0,\infty)\to\R which are such that \phi>0 on (0,\infty) , but that in addition \phi(0)=0 with \phi'(0)>0 . In order to appropriately cope with the diffusion degeneracies thereby included, this study separately examines the Neumann problem for the linear equation V_{t} = \Delta V + \nabla\cdot ( a(x,t)V) + b(x,t)V and establishes a statement on how pointwise positive lower bounds for nonnegative solutions depend on the supremum and the mass of the initial data, and on integrability features of a and b . This is thereafter used as a key tool in the derivation of a result on global existence of solutions to the equation above, smooth and classical for positive times, under the mere assumption that the suitably regular initial data be nonnegative in both components. Apart from that, these solutions are seen to stabilize toward some equilibrium, and as a qualitative effect genuinely due to degeneracy in diffusion, a criterion on initial smallness of the second component is identified as sufficient for this limit state to be spatially nonconstant.

Depleting the signal: Analysis of chemotaxis‐consumption models—A survey - Lankeit, Johannes; Winkler, Michael (Studies in Applied Mathematics)
Abstract We give an overview of analytical results concerned with chemotaxis systems where the signal is absorbed. We recall results on existence and properties of solutions for the prototypical chemotaxis‐consumption model and various variants and review more recent findings on its ability to support the emergence of spatial structures.
Keywords: Applied Mathematics

Stability vs.~instability of singular steady states in the parabolic-elliptic Keller-Segel system on $\R^n$ - Colasuonno, Francesca; Winkler, Michael (ANNALI SCUOLA NORMALE SUPERIORE - CLASSE DI SCIENZE)

Finite-Set Direct Torque Control via Edge Computing-Assisted Safe Reinforcement Learning for a Permanent Magnet Synchronous Motor - Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Deep Q Direct Torque Control with a Reduced Control Set Towards Six-Step Operation of Permanent Magnet Synchronous Motors - Haucke-Korber, Barnabas; Schenke, Maximilian; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Gym-Electric-Motor (GEM) Control: An Automated Open-Source Controller Design Suite for Drives - Book, Felix; Traue, Arne; Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Inverse procedure for measuring piezoelectric material parameters using a single multi-electrode sample - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Meihost, Lars; Kuhlmann, Henrik; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Journal of Sensors and Sensor Systems)

Inverse procedure for the identification of piezoelectric material parameters supported by dense neural networks - Claes, Leander; Meihost, Lars; Jurgelucks, Benjamin

Parameter Identification of Piezoelectrics improved by Neural Networks - Jurgelucks, Benjamin

Parameter identification in piezoelectricity based on all-at-once and reduced regularization - Kuess, Raphael

Investigating Speaker Embedding Disentanglement on Natural Read Speech - Kuhlmann, Michael; Meise, Adrian Tobias; Seebauer, Fritz; Wagner, Petra; Häb-Umbach, Reinhold (Speech Communication; 15th ITG Conference)

Green Light Photoelectrocatalysis with Sulfur‐Doped Carbon Nitride: Using Triazole‐Purpald for Enhanced Benzylamine Oxidation and Oxygen Evolution Reactions - Jerigova, Maria; Markushyna, Yevheniia; Teixeira, Ivo F.; Badamdorj, Bolortuya; Isaacs, Mark; Cruz, Daniel; Lauermann, Iver; Muñoz‐Márquez, Miguel Ángel; Tarakina, Nadezda V.; Lopez Salas, Nieves; Savateev, Oleksandr; Jimenéz‐Calvo, Pablo (Advanced Science)
Abstract Materials dictate carbon neutral industrial chemical processes. Visible‐light photoelectrocatalysts from abundant resources will play a key role in exploiting solar irradiation. Anionic doping via pre‐organization of precursors and further co‐polymerization creates tuneable semiconductors. Triazole derivative‐purpald, an unexplored precursor with sulfur (S) container, combined in different initial ratios with melamine during one solid‐state polycondensation with two thermal steps yields hybrid S‐doped carbon nitrides (C 3 N 4 ). The series of S‐doped/C 3 N 4 ‐based materials show enhanced optical, electronic, structural, textural, and morphological properties and exhibit higher performance in organic benzylamine photooxidation, oxygen evolution, and similar energy storage (capacitor brief investigation). 50M‐50P exhibits the highest photooxidation conversion (84 ± 3%) of benzylamine to imine at 535 nm – green light for 48 h, due to a discrete shoulder (≈700) nm, high sulfur content, preservation of crystal size, new intraband energy states, structural defects by layer distortion, and 10–16 nm pores with arbitrary depth. This work innovates by studying the concomitant relationships between: 1) the precursor decomposition while C 3 N 4 is formed, 2) the insertion of S impurities, 3) the S‐doped C 3 N 4 property‐activity relationships, and 4) combinatorial surface, bulk, structural, optical, and electronic characterization analysis. This work contributes to the development of disordered long‐visible‐light photocatalysts for solar energy conversion and storage.

Tin (II) Chloride Salt Melts as Non‐Innocent Solvents for the Synthesis of Low‐Temperature Nanoporous Oxo‐Carbons for Nitrate Electrochemical Hydrogenation - Zheng, Xinyue; Tian, Zhihong; Bouchal, Roza; Antonietti, Markus; Lopez Salas, Nieves; Odziomek, Mateusz (Advanced Materials)
Abstract Carbonaceous electrocatalysts offer advantages over metal‐based counterparts, being cost‐effective, sustainable, and electrochemically stable. Their high surface area increases reaction kinetics, making them valuable for environmental applications involving contaminant removal. However, their rational synthesis is challenging due to the applied high temperatures and activation steps, leading to disordered materials with limited control over doping. Here, a new synthetic pathway using carbon oxide precursors and tin chloride as a p‐block metal salt melt is presented. As a result, highly porous oxygen‐rich carbon sheets (with a surface area of 1600 m 2 g −1 ) are obtained at relatively low temperatures (400 °C). Mechanistic studies reveal that Sn(II) triggers reductive deoxygenation and concomitant condensation/cross‐linking, facilitated by the Sn(II) → Sn(IV) transition. Due to their significant surface area and oxygen doping, these materials demonstrate exceptional electrocatalytic activity in the nitrate‐to‐ammonia conversion, with an ammonia yield rate of 221 mmol g −1 h −1 and a Faradic efficiency of 93%. These results surpass those of other carbon‐based electrocatalysts. In situ Raman studies reveal that the reaction occurs through electrochemical hydrogenation, where active hydrogen is provided by water reduction. This work contributes to the development of carbonaceous electrocatalysts with enhanced performance for sustainable environmental applications.

Oxygen‐Rich Carbon Nitrides from an Eutectic Template Strategy Stabilize Ni, Fe Nanosites for Electrocatalytic Oxygen Evolution - Li, Chun; Lepre, Enrico; Bi, Min; Antonietti, Markus; Zhu, Junwu; Fu, Yongsheng; Lopez Salas, Nieves (Advanced Science)
Abstract Functionalized porous carbons are central to various important applications such as energy storage and conversion. Here, a simple synthetic route to prepare oxygen‐rich carbon nitrides (CNOs) decorated with stable Ni and Fe‐nanosites is demonstrated. The CNOs are prepared via a salt templating method using ribose and adenine as precursors and CaCl 2 ·2H 2 O as a template. The formation of supramolecular eutectic complexes between CaCl 2 ·2H 2 O and ribose at relatively low temperatures facilitates the formation of a homogeneous starting mixture, promotes the condensation of ribose through the dehydrating effect of CaCl 2 ·2H 2 O to covalent frameworks, and finally generates homogeneous CNOs. As a specific of the recipe, the condensation of the precursors at higher temperatures and the removal of water promotes the recrystallization of CaCl 2 ( T < T m = 772 °C), which then acts as a hard porogen. Due to salt catalysis, CNOs with oxygen and nitrogen contents as high as 12 and 20 wt%, respectively, can be obtained, while heteroatom content stayed about unchanged even at higher temperatures of synthesis, pointing to the extraordinarily high stability of the materials. After decorating Ni and Fe‐nanosites onto the CNOs, the materials exhibit high activity and stability for electrochemical oxygen evolution reaction with an overpotential of 351 mV.

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Abstract Self‐templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m 2 g −1 ) originating from low activity of metal cations (e.g., K + or Na + ) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo‐carbons with large SSA of the order of 3000 m 2 g −1 , pore volume approaching 2 cm 3 g −1 , tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs + as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo‐carbons show record‐high CO 2 uptake of 8.71 mmol g −1 and an ultimate specific capacitance of 313 F g −1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid‐state chemistry.

Template-induced graphitic nanodomains in nitrogen-doped carbons enable high-performance sodium-ion capacitors - ACCEPTED MANUSCRIPT - Lopez Salas, Nieves; Li, Chun; Song, Zihan; Liu, Minliang; Lepre, Enrico; Antonietti, Markus; Zhu, Junwu; Liu, Jian; Fu, Yongsheng
Sodium-ion capacitors (SICs) have great potential in energy storage due to their low cost, the abundance of Na, and the potential to deliver high energy and power simultaneously. This paper demonstrates a template-assisted method to induce graphitic nanodomains and micro-mesopores into nitrogen-doped carbons. This study elucidates that these graphitic nanodomains are beneficial for Na+ storage. The obtained N-doped carbon (As8Mg) electrode achieved a reversible capacity of 254 mA h g−1 at 0.1 A g−1. Moreover, the As8Mg-based SIC device achieves high combinations of power/energy densities (52 W kg−1 at 204 Wh kg−1 and 10,456 W kg−1 at 51 Wh kg−1) with outstanding cycle stability (99.7% retention over 10000 cycles at 0.2 A g−1). Our findings provide insights into optimizing carbon’s microstructure to boost sodium storage in the pseudo-capacitive mode.
Keywords: sodium ion capacitor; anode; template; N-doped carbons; graphitic nanodomains

Dynamic conditioning of two particle discrete-time quantum walks - Pegoraro, Federico; Held, Philip; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physica Scripta)
In real photonic quantum systems losses are an unavoidable factor limiting the scalability to many modes and particles, restraining their application in fields as quantum information and communication. For this reason, a considerable amount of engineering effort has been taken in order to improve the quality of particle sources and system components. At the same time, data analysis and collection methods based on post-selection have been used to mitigate the effect of particle losses. This has allowed for investigating experimentally multi-particle evolutions where the observer lacks knowledge about the system's intermediate propagation states. Nonetheless, the fundamental question how losses affect the behaviour of the surviving subset of a multi-particle system has not been investigated so far. For this reason, here we study the impact of particle losses in a quantum walk of two photons reconstructing the output probability distributions for one photon conditioned on the loss of the other in a known mode and temporal step of our evolution network. We present the underlying theoretical scheme that we have devised in order to model controlled particle losses, we describe an experimental platform capable of implementing our theory in a time multiplexing encoding. In the end we show how localized particle losses change the output distributions without altering their asymptotic spreading properties. Finally we devise a quantum civilization problem, a two walker generalisation of single particle recurrence processes.